Soliton Mode-Locked Erbium-Doped Fiber Laser Using Non-Conductive Graphene Oxide Paper - Ismail, M.A.; Ahmad, Harith; Harun, Sulaiman Wadi (Institute of Electrical and Electronics Engineers (IEEE), 2014)
A femtosecond mode-locked soliton erbium-doped fiber laser (EDFL) is demonstrated using a commercially available nonconductive graphene oxide paper as a saturable absorber. The paper that is sandwiched between two fiber ferrules acts as a mode-locker. The EDFL generates a soliton mode-locked pulse train with a repetition rate of 15.62 MHz and pulsewidth of 680 fs. It is observed that the fiber laser has a low pulsing threshold as well as low damage threshold. The pulse energy and peak power are 0.0085 nJ and 11.85 W, respectively. The easy fabrication of graphene oxide paper should promote its potential application in ultrafast photonics.